Effects of flaxseed extract on the viability of stem cells from human exfoliated deciduous teeth - Mokhtar@Makhtar, Khairani Idah; Nordin, Nur Sazwi; Mustafa Al-Ahmad, Basma Ezzat; Lestari, Widya; Arief Ichwan, Solachuddin Jauhari; Darnis, Deny Susanti; Kannan, Thirumulu Ponnuraj (2016)
Purpose: To determine the effects different concentrations of flaxseed crude extract on the viability of stem cells from human exfoliated deciduous teeth (SHED). Methods: Whole flaxseeds were ground and extracted using 99.8% ethanol in a Soxhlet chamber. The crude extract was kept in a closed container and stored at 4°C until further use. SHED (ALLCells, USA) was cultured and maintained in Alpha-MEM supplemented with FBS and antibiotics at 37°C in a CO2 incubator. Cells were trypsinised and 1000 cells were seeded in a 96-well plate. After 24 hours of incubation, SHED were treated with different concentrations of Flaxseed crude extract (0.0-16 mg/ml). The cell viability was determined using MTT assay after 3 days’ incubation. The morphology of the cells was also observed. Results: The SHED viability was more than 100% until a concentration of 8 mg/ml of flaxseed extract and an IC50 and IC25 values at 11.85 mg/ml and 10.82 mg/ml respectively which lead to cell death. Additionally, there were also morphological changes when treated with these different concentrations. Cells appeared healthy and maintained the fibroblast-like shape at 4 mg/ml. However, at 8 mg/ml, some of the cells cytoplasm started to demonstrate vacuolation and granulation and at 16 mg/ml, all cells appeared non-viable. Conclusions: The cell viability of SHED was more than 100% until 8 mg/ml of the flaxseed extract consistent with the morphological changes indicating the potential of this extract to be used further in research relating to tissue engineering involving stem cells.